Low platelet count during pregnancy - Trupti Agrawal; Aditi Kaundinya; Anuya Pawde (MGM Journal of Medical Sciences, 2025)
Thrombocytopenia, a platelet count below 150,000/mm3, is the second most common hematological disorder during pregnancy, following anemia. It affects approximately 7–10% of pregnant women and may result from physiological changes or underlying pathological conditions, some of which can have serious maternal and fetal consequences. This study was conducted at a tertiary care center in Navi Mumbai to assess the causes, management, and maternal outcomes associated with thrombocytopenia in pregnancy. Over one year, 12 cases were examined. Among these, 50% were diagnosed with gestational thrombocytopenia (GT), 16% with immune thrombocytopenic purpura (ITP), another 16% with dengue-related thrombocytopenia, 10% with hypertensive disorders of pregnancy, and 8% with hereditary thrombocytopenia. Treatment strategies varied based on the underlying cause, including platelet transfusions, corticosteroids, and intravenous immunoglobulin. While GT was typically mild with favorable outcomes, more severe conditions such as ITP and hypertensive disorders required coordinated, multidisciplinary care. Prompt diagnosis, targeted treatment, and planned institutional deliveries were crucial in minimizing complications and achieving positive maternal and fetal outcomes.